Effect of coagulant aid (P-Floc) in treatment of dye wastewater: article - Roslan, Siti Zaharah; Noor Ismail, Kamariah (2017)
This study was conducted to investigate the effect of solution pH and dosage of cationic polyelectrolyte, P-floc as a flocculant in treatment of dye wastewater and to characterize the quality of treated dye wastewater. For removal dyes in wastewaters, different treatment ways such as adsorption, coagulation-flocculation, chemical oxidation, photo-degradation and biological exchange are useful. Among the above methods, the process of coagulationflocculation is widely used in the manufacture of dyes from industrial waste water. Typically, alum or a grounded metal used to treat dye wastewater. But the manufacture of aluminium alum are contributing to the pollution of wastewater that can negatively affect our ecosystem, especially to aquatic life. Natural flocculants is very useful to solve this problem. Therefore, p-floc is very useful in the treatment of dye wastewater instead of alum to prevent the use of metal-based. The experiment was conducted using Jar test method to determine the optimum pH value, coagulant and flocculant dose. In this research, the study was conducted by varying p-floc dosage in between 1.0 ml to 3.5 ml in order to study their effect in flocculation and the optimum condition for each parameter. Parameters such as turbidity, Chemical Oxygen Demand (COD), Total Suspended Solid (TSS), Colour, Phosphate, Sulphate, DPD Total Chlorine, DPD Free Chlorine and heavy metals have been evaluated. It is discovered that decolourization of dye was occurred between pH 6 to 8 and between dosage P-floc 2.5 to 3mL. The optimum pH is chosen at pH 7. The results obtained were based on turbidity, Chemical Oxygen Demand (COD), Total Suspended Solid (TSS), Colour, Phosphate, Sulphate, DPD Total Chlorine, DPD Free Chlorine and heavy metals. Based on this fact, P-floc has a big potential to become as a coagulant aid to treat dye wastewater.